THE IMPLEMENTATION OF FIX UP STRATEGY STUDENTS’ READING COMPREHENSION SKIL - Asnidah, Sri; Paturusi, M. Arief; Burhanuddin, Wildhan (English Language Teaching Methodology, 2024)
The objective of the study is to find out whether the use of Fix-Up Strategy enhance the students’ in reading comprehension in terms of literal and interpretative comprehensions. The research method is pre-experimental design with pre-test and post-test as quantitative research. The population of the research was students of SMP Unismuh Makassar. The total number of sample was 22 students which chosen by using purposive sampling. The instrument used to collect data in reading comprehension was reading text (narrative text).